2009
DOI: 10.1002/jctb.2317
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel from activated sludge through in situ transesterification

Abstract: BACKGROUND:The microbial biomass present in activated sludge contains lipidic compounds that can be used as biodiesel feedstock. In this study, the production of biodiesel from activated sludge from Tuscaloosa, AL was optimized based on the yield of fatty acid methyl esters (FAMEs). In situ transesterification was used with sulfuric acid as catalyst. A general factorial design of 4 × 6 × 5 for temperature, methanol to sludge ratio and catalyst concentration, respectively, was considered for optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 24 publications
6
82
1
2
Order By: Relevance
“…Previous studies have demonstrated the potential of primary and secondary sludge from municipal wastewater treatment plants as biodiesel feedstock. For instance, Dufreche et al (2007), Mondala et al (2009), Revellame et al (2010 and Olkiewicz et al (2015) reported that the biodiesel generated from wastewater treatment plants sludge mainly contains methyl esters of palmatic acid (C16:0), palmitoleic acid (C16:1), stearic acid (C18:0), oleic acid (C18:1), and linoleic acid (C18:2). This biodiesel composition is similar to that of some vegetable oil biodiesel such as olive, corn and rapeseed (Ramos et al, 2009), which had the better properties because of the greater monounsaturated content.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the potential of primary and secondary sludge from municipal wastewater treatment plants as biodiesel feedstock. For instance, Dufreche et al (2007), Mondala et al (2009), Revellame et al (2010 and Olkiewicz et al (2015) reported that the biodiesel generated from wastewater treatment plants sludge mainly contains methyl esters of palmatic acid (C16:0), palmitoleic acid (C16:1), stearic acid (C18:0), oleic acid (C18:1), and linoleic acid (C18:2). This biodiesel composition is similar to that of some vegetable oil biodiesel such as olive, corn and rapeseed (Ramos et al, 2009), which had the better properties because of the greater monounsaturated content.…”
Section: Introductionmentioning
confidence: 99%
“…Methanol was removed from samples using a TurboVap LV evaporator (CaliperLife Sciences, Hopkinton, MA, USA) with a stream of N 2 at 15 psi and a bath temperature of 45°C as it was previously done in the literature [31]. Samples were then placed in storage at 4°C until GC analysis.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…This is due to the negative effect of catalyst amount, probably caused by polymerization of unsaturated fatty acids. 34 The maximum crude biodiesel yield of 69.36 % (w/w, base on lipid weight) could be calculated under the condition at 70 ºC for 10 hrs reaction time with biomass to methanol ratio of 1:22.07 with catalyst amount of 5.46 % using MINITAB ® 16 software (Minitab Inc., Pennsylvania, USA). 69.11±1.16 % of actual experimental yield from the process was showed good agreement with 69.36 % of the theoretical yield from the proposed model.…”
Section: Optimization Of Biodiesel Production By Response Surface Metmentioning
confidence: 99%